Al-i'jaz al-'ilmi fi al-hadith: Case studies of cupping therapy in modern medical research - bin Kurdian, Nur Kholis; Hasanah, Ainun Nur; Pamungkas, Akhmad Yanuar Fahmi (Communications in Humanities and Social Sciences, 2024)
Al-i'jaz al-'ilmi is news that comes from the Qur'an or hadith about a fact that has been proven empirically through modern scientific research which in the past has not been scientifically revealed. Among the news from the prophet's hadith that is studied in this research is the hadith about cupping therapy that has been recommended by the Prophet shallallahu ‘alaihi wasallam since 14 centuries ago. Since modern scientific research can be conducted in a variety of ways and produce evidence that may not be conclusive, it is necessary to understand the categorical level of evidence derived from modern scientific research in order to be declared as al-i'jaz al-'iImi (scientific miracle). Unfortunately, research on this topic is still limited. On the other hand, such knowledge is important to enrich the information needed in the context of the science of ma'ani al-hadith and the enhancement of faith or spirituality of modern Islamic society. The purpose of this study is to reveal the categories of modern research findings to be declared as al-i'jaz al-'ilmi in the context of health. This research is library research. To see the implementation of the categories compiled, categorization is applied to medical research datasets related to cupping therapy. The results showed that the categorization of al-i'jaz al-ilmi fi al-hadith research includes; the existence of a valid hadith text discussing this matter, then there is a clear signal in the hadith text about scientific facts, then the existence of authentic scientific facts, meaning that it has been tested, not just a theory.  Based on this categorization, the medical research dataset related to cupping therapy falls into this category. This shows that medical research evidence related to cupping therapy and medical research is part of al-i'jaz al-ilmi fi al-hadith.